Teachers’ Experiences of Implementing Differentiated Instruction in Elementary School - Khoirudin, Asmi; Khori, Ahmad (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
Differences in students’ readiness, interests, confidence, and ways of learning require teachers to adjust instruction without reducing shared learning goals. This study explored the experiences of Grade IV, V, and VI classroom teachers in understanding, planning, implementing, and responding to the perceived benefits, constraints, and support needs of differentiated instruction. A qualitative phenomenological design was employed at SDN 202 Suryalaya, Bandung, Indonesia, with three classroom teachers purposively selected as participants. Primary data were generated through semi-structured interviews, while classroom observations and limited document review provided supporting evidence. The data were analyzed thematically through repeated reading, initial coding, category development, cross-participant comparison, theme construction, and interpretation. The findings show that teachers understood differentiated instruction as equitable adjustment rather than separate teaching for every student. They used initial assessments and knowledge of students’ characteristics to modify materials, grouping, scaffolding, activities, and learning products. Teachers perceived that these adjustments supported participation, confidence, and the visibility of abilities that were less apparent in written tasks. Implementation was constrained by preparation time, class size, limited resources, administrative demands, and difficulties in distributing attention. Sustainable implementation requires collaborative planning, adaptable learning resources, concise progress records, and classroom-based professional development.